BIG DATA AND FORMATION OF SOCIAL CAPITAL - Kobzev , Ihor; Melnikov , Oleksandr; Orlov , Oleksandr (Theory and Practice of Public Administration, 2019)
In order to ensure the country’s competitiveness, it is necessary to accomplish a digital revolution, and above all – in social data. In order to become a full-fledged participant of this revolution in the use of social data, one needs to reject the old “consumer” mindset and switch to a new thinking – the thinking of an active creator of social data.The pare objective is to outline the ways for the use of innovative technology of Big Data for social capital formation.Recent research and publications analysis. In the globalized world, the increasing share of non-productive losses is made up by the so-called transaction losses or costs. Along with the economic context, attempts have been made to use the theory of transaction costs in politics, although the object of exchange is not quite obvious. Thus, in the course of selection, a voter exchanges his/her vote for the election promises of one of the candidates, which is related to the transaction costs of collecting information. But in any case, it is clear that transaction losses are inversely related to the reputation of political actors – the lower their reputation, the greater the transaction losses.Presenting main material. In many effective communities, reputation is of paramount importance. But, as they say, it’s hard to earn, while losing is very easy, because in traditional communities only “significant” – and thus quite rare – deeds are taken into account. Therefore, in the pre-information era, only heroes i.e. representatives of elites had a good reputation or social capital.Conclusions of the research and prospects for further exploration. Thus it has been established that one of the effective ways to increase the competitiveness of Ukraine in today’s global world is to reduce transactional losses of society through the introduction of tools for accounting and accumulation of social capital, providing citizens with opportunities to manage and use it. Apparently, for this purpose it is necessary to solve a whole range of legislative problems; yet, it is already possible to begin creating conditions and encouraging respectable citizens.